Archetypal Elements in Brand Narratives : Case: Apple Corporation - Lyytikäinen, Petri (fi=Turun yliopisto|en=University of Turku|, 2017)
The purpose of this study was to examine archetypal elements in brand narratives. Arcetypal elements are certain generally known forms and characters part of the common unconsciousness of humans. The reason these archetypal elements were chosen under examination is the fact that through them the receiver of the narrative relates to the story as the receiver is able to recognize familiar and predictable actions in the narrative. This increases the immersion into the story as the audience is able to complete the story without it being laid clearly in front of them. The archetypal elements forming the basis for this study consist of seven archetypal storylines and twelve archetypal characters. There is no single uncontradicted categorization of these, but after reviewing the different classifications Christopher Booker’s classification of seven archetypal plotlines were chosen. These plotlines are: 1) overcoming the monster, 2) rags to riches 3) the quest 4) voyage and return 5) comedy 6) tragedy and 7) rebirth. Often more complex narratives might employ several if not all of the aforementioned storylines. The story consists not only actions and happenings that form events and the storyline, but also characters and settings; the existents. Which often go hand in hand in commercials where the limited time forces the nature of the characters to be established also through the setting. The classification for the character archetypes chosen for this study is based on Carl Jung’s study on characters appearing recurrently in fables, sagas and stories passed on generations. This classification of twelve character archetypes were used for this study. The categorization is based on four human desires: yearn for paradise, leave a mark, connect to others and maintain stability. Through these preconditions the Apple brand narrative was reviewed by examining and cataloging over two hundred Apple commercials throughout the history of the brand. This enabled the researcher to examine the use of archetypal storylines and characters in Apple brand narrative and form an analysis on the coherence of Apple narrative and changes to it over the years. To summarize the findings and managerial implications of this study, the case indicates that as long as the simple core message and ideology of the company is constantly present in the narrative and is not changing suddenly the narrative remains coherent despite the usage of various types of commercials. Another thing that holds the narrative together is the conflict which is paramount in keeping the narrative and company interesting and appealing to consumers. The usage of strong and recognizable archetypal characters and storylines help in making the narrative interesting as it offers the consumers a point of relation and the consumer is not lost in the sense making process as they have the ability to fill in the gaps based on the resources of their collective unconsciousness.